ANALISIS DETERMINAN PELAPORAN INSIDEN KESELAMATAN PASIEN OLEH PENANGGUNG JAWAB RUANGAN VK DI RUMAH SAKIT - Eti Sulastri; Syarif Hidayat Nasir; Hudriyani Jamal (Journal Bidan, 2023)
The lack of a culture of reporting patient safety incidents causes a high number of errors when taking action because ten near-miss incidents will lead to one unexpected incident. Patient Safety Incident Reporting (IKP) can be used as a learning process that can prevent the recurrence of errors and will ultimately improve patient safety and the quality of nursing care and services in hospitals. A systematic review was carried out, which aimed to identify factors that influence the reporting of IKP by the person in charge of the room in a hospital. The method in this research uses article searches through databases such as ProQuest, ScienceDirect, and SPRINGER LINK with the keywords: patient safety incident reporting; education; work experience; perception; attitude. From the search results, 1055 were obtained, then screening was carried out, 4 journals were found that met the PICO inclusion criteria, problems and research objectives. The results of this study show that based on 4 journals, generally significant factors in reporting IKP are lack of knowledge, fear and worry and the perception of not reporting uninjured patients.